2009
DOI: 10.1159/000215729
|View full text |Cite
|
Sign up to set email alerts
|

Fiberoptic Bronchoscopy in Neonatal and Pediatric Intensive Care Units: A 5-Year Experience

Abstract: Objectives: To determine the value and safety of fiberoptic bronchoscopy in neonatal and pediatric intensive care units (NICUs, PICUs). Subject and Methods: A total of 53 fiberoptic bronchoscopy procedures on 47 patients were reviewed. Bronchoalveolar lavage (BAL) was performed in 23 patients. Results: The primary diseases were pneumonia (n = 16), foreign body aspiration (n = 14), congenital airway abnormality (n = 12), trauma and/or following operations (n = 4) and Guillain-Barré syndrome (n = 1). The major b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 37 publications
5
33
0
2
Order By: Relevance
“…De Blic et al [4] reported that in children with CHD, FFB findings of external compression of the airways by cardiovascular anomalies prompted earlier cardiac surgery in 50% (5/10) [4] . Twenty-one studies reported an overall diagnostic yield of 82% using FFB (range 45.2%-100%; 3791/4 622) [3][4][5][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . [27] , 2011 [20,24,31] .…”
Section: Diagnostic Yield Of Ffbmentioning
confidence: 99%
See 3 more Smart Citations
“…De Blic et al [4] reported that in children with CHD, FFB findings of external compression of the airways by cardiovascular anomalies prompted earlier cardiac surgery in 50% (5/10) [4] . Twenty-one studies reported an overall diagnostic yield of 82% using FFB (range 45.2%-100%; 3791/4 622) [3][4][5][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . [27] , 2011 [20,24,31] .…”
Section: Diagnostic Yield Of Ffbmentioning
confidence: 99%
“…[27] , 2011 [20,24,31] . Lower airway findings included airway stenosis, compression, malacia, mucus plugs, thrombus, and malpositioned endotracheal tube [3,14,15,17,18,20,21,23,24,31,32] . The diagnostic yield of FFB varied amongst different patient populations.…”
Section: Diagnostic Yield Of Ffbmentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic principle for this condition is timely full drainage of sputum and blood at early stage. Although use of an artificial airway and fiber bronchoscopy for the treatment of severe traumatic atelectasis with dyspnea or massive hemoptysis is now accepted [2,3], there still remain several problems as follows: first, for young patients with atypical manifestations and sufficient compensation of pulmonary function, it is difficult to make the decision to create an artificial airway to drain sputum and blood. But the pathological injury might be aggravated gradually without timely drainage; second, manipulation of the fiber bronchoscope through the nasal cavity may lead to patients' resistance and breath-holding, which can make it difficult for the patients to tolerate repeated treatment within a short period of time; on the other hand, breath-holding can increase the airway pressure, thereby exacerbating the original airway injury, or even b u r s t , w h i c h m a y c a u s e a p n e u m o t h o r a x o r pneumomediastinum.…”
Section: Introductionmentioning
confidence: 99%